Happiness, Economics and Politics 2009
DOI: 10.4337/9781849801973.00012
|View full text |Cite
|
Sign up to set email alerts
|

Happiness when Temptation Overwhelms Willpower

Abstract: The economics of happiness is applied to further the understanding of important consumption decisions in which limited willpower is often argued to lead to suboptimal choices. Based on individuals' judgments of the quality of their lives, it is, in principle, possible to derive whether some observed behavior is suboptimal and is therefore reducing a person's welfare. We discuss the key characteristics and the normative basis of the approach including the evaluation metric and issues of empirical identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
3
6
0
Order By: Relevance
“…Controlling for many individual characteristics, it is found that the more time people spend watching TV, the lower is their reported satisfaction with life, ceteris paribus. The result of the econometric analysis is consistent with the hypothesis that heavy TV viewers suffer significant reductions in their utility because they are 14 Other possible illustrations would be to smoking (Gruber and Mullainathan 2005) or to obesity (Stutzer 2009;Oswald and Powdthavee 2007). 15 In economics, the notion of inconsistent time preference is most prominently formulated in models of (quasi) hyperbolic discounting (see, e.g., Laibson 1997).…”
Section: Limited Self-control and Individual Well-beingsupporting
confidence: 61%
“…Controlling for many individual characteristics, it is found that the more time people spend watching TV, the lower is their reported satisfaction with life, ceteris paribus. The result of the econometric analysis is consistent with the hypothesis that heavy TV viewers suffer significant reductions in their utility because they are 14 Other possible illustrations would be to smoking (Gruber and Mullainathan 2005) or to obesity (Stutzer 2009;Oswald and Powdthavee 2007). 15 In economics, the notion of inconsistent time preference is most prominently formulated in models of (quasi) hyperbolic discounting (see, e.g., Laibson 1997).…”
Section: Limited Self-control and Individual Well-beingsupporting
confidence: 61%
“…Recent technological developments such as digital recorders, smart television sets, and streaming services such as Netflix have (1) threatened to make the concept of scheduled viewing obsolete; (2) disconnected the media content from the media platform, creating access anywhere at any time; and (3) provided viewers with a never-ending flow of varying content. Therefore, the observation that television viewing offers a tempting, immediate gratification is even more relevant in the contemporary viewing experience (Frey, Benesch, & Stutzer, 2007;Stutzer, 2009). There is now a larger and continuous flow of temptations than ever, challenging people's ability to withstand them (Panek, 2013).…”
Section: Television Viewing As a Self-control Issuementioning
confidence: 99%
“…It is therefore important to know how damaging it actually is and what can be done about it. A negative relationship between overconsumption and life satisfaction exists, for example for alcohol consumption (Veenhoven 2003), obesity (Stutzer 2009). Benesch et al (2010) show that for many people, it is tempting to view TV rather than to pursue more engaging activities, because of its immediate benefits at negligible immediate marginal costs.…”
Section: Great Achievementsmentioning
confidence: 99%